2021
DOI: 10.1017/cjn.2021.197
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers and Intracranial Hemorrhage after Endovascular Thrombectomy

Abstract: Background: Intracranial hemorrhage after endovascular thrombectomy is associated with poorer prognosis compared with those who do not develop the complication. Our study aims to determine predictors of post-EVT hemorrhage – more specifically, inflammatory biomarkers present in baseline serology. Methods: We performed a retrospective review of consecutive patients treated with EVT for acute large vessel ischemic stroke. The primary outcome of the study is the presence of ICH on the post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…20,21 In previous studies, the HT rate after MT ranged from 29.4% to 42.6% and the sICH rate ranged from 6.3% to 12.4%. [22][23][24][25] In our study, the HT rate was 41.9% and the sICH rate was 10.3%, in line with the results of previous studies. An observational study reported a PH rate of 25.7%, 26 which is close to our rate of 26.5%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…20,21 In previous studies, the HT rate after MT ranged from 29.4% to 42.6% and the sICH rate ranged from 6.3% to 12.4%. [22][23][24][25] In our study, the HT rate was 41.9% and the sICH rate was 10.3%, in line with the results of previous studies. An observational study reported a PH rate of 25.7%, 26 which is close to our rate of 26.5%.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, the HT rate after MT ranged from 29.4% to 42.6% and the sICH rate ranged from 6.3% to 12.4%. 22 , 23 , 24 , 25 In our study, the HT rate was 41.9% and the sICH rate was 10.3%, in line with the results of previous studies. An observational study reported a PH rate of 25.7%, 26 which is close to our rate of 26.5%.…”
Section: Discussionsupporting
confidence: 92%
“…However, the systematic review provided unclear results; although a higher PLR was observed in patients with sICH by both Topcuoglu et al and Inanc & Inana, this was only significant in the former study. 18 , 21 Additionally, Diestro et al 32 reported that admission PLR was not significantly associated with sICH in adjusted analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Higher levels of CRP also affected the sICH incidence [46][47][48][49]. An association of some serological markers with post-EVT haemorrhage has also been demonstrated, with, among these, low platelets and white blood cells, along with high neutrophil counts, being risk factors of HT [50].…”
Section: Haemorrhagic Transformationmentioning
confidence: 89%
“…Conflicting data exists on the association of hyperlipidemia and platelet-to-lymphocyte ratio (PLR) with HT. Both high and low values of these parameters have been indicated as risk factors for haemorrhagic AIS transformation by different authors [27,29,33,50]. The exact mechanisms of how biochemical and serological parameters influence post-EVT HT occurrence is not well understood.…”
Section: Haemorrhagic Transformationmentioning
confidence: 99%